ROLES OF ARBUSCULAR MYCORRHIZAL FUNGI ON GROWTH AND NUTRIENT ACQUISITION OF PEACH (PRUNUS PERSICA L. BATSCH) SEEDLINGS - Q.-S. Wu; G.-H. Li; Y. N. Zou (Journal of Animal and Plant Sciences, 2011)
Arbuscular mycorrhizal fungi (AMF) can form mutualistic symbioses with the roots of 80% of plants, which increase soil water and nutrient uptake for the host plants. However, little information is known on potential roles of different AMF for growth and nutrient acquisition of peach. In a potted experiment, we determined the growth performance, nutrient concentrations and mycorrhizal nutrient efficiency of the peach (Prunus persica L. Batsch) seedlings inoculated with Glomus mosseae, G. versiforme, and Paraglomus occultum, respectively. After 100 days of mycorrhizal inoculations, mycorrhizal colonization of one-year-old seedlings ranged from 23.4% to 54.9%. Generally, the formed mycorrhizal symbiosis significantly improved plant growth performance, such as plant height, stem diameter, shoot, root or total dry weight. Compared with the non-AMF seedlings, a range of 9.2–28.5% K of leaves, 86.0–120.9% K of roots, 118.3–417.3% Ca of leaves, 31.9–55.7% Mg of leaves, 76.6–140.4% Mg of roots, 101.3–169.6% Fe of leaves, 37.6–66.5% Fe of roots, 178.3–321.7% Cu of roots, 33.3–91.7% Mn of roots, 50.0–58.3% Zn of leaves, and 200.0–450.0% Zn of roots were respectively higher in the mycorrhizal seedlings. The mycorrhizal benefit role on nutrient uptake generally was the best in the G. mosseae treatment. It suggests that arbuscular mycorrhizas could improve growth performance and part nutrient acquisition of peach, which were absolutely dependent on AMF species.
Keywords: arbuscular mycorrhiza; peach; mycorrhizal nutrient efficiency; nutrient uptake.